2003
DOI: 10.1074/jbc.m205726200
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 RNA Dimerization Initiation Site Is Structurally Similar to the Ribosomal A Site and Binds Aminoglycoside Antibiotics

Abstract: Human immunodeficiency virus (HIV) genomic RNA is packaged into virions as a dimer. The first step of dimerization is the formation of a kissing-loop complex at the so-called dimerization initiation site (DIS). We found an unexpected and fortuitous resemblance between the HIV-1 DIS kissing-loop complex and the eubacterial 16 S ribosomal aminoacyl-tRNA site (A site), which is the target of aminoglycoside antibiotics. Similarities exist not only at the primary and secondary structure level but also at the tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 42 publications
7
66
0
Order By: Relevance
“…This RNA/drug complex involves a 23-nt RNA homodimer, which promotes viral genome dimerization and is recognized by aminoglycosides (Ennifar et al 2003(Ennifar et al , 2007bBernacchi et al 2007;Freisz et al 2008). In parallel to an extensive but unsuccessful search for heavy atom derivatives, we attempted to determine the structure using 5-halogen-pyrimidine derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…This RNA/drug complex involves a 23-nt RNA homodimer, which promotes viral genome dimerization and is recognized by aminoglycosides (Ennifar et al 2003(Ennifar et al , 2007bBernacchi et al 2007;Freisz et al 2008). In parallel to an extensive but unsuccessful search for heavy atom derivatives, we attempted to determine the structure using 5-halogen-pyrimidine derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…The relevance of bulged-out conformations in solution is supported by the binding of aminoglycoside antibiotics to the DIS kissing complex with bulged-out 5 0 flanking bases. 15,71,72 This binding was first predicted based on the structural similarity between DIS kissing complex and bacterial 16S ribosomal A site, and then it was confirmed by the experiments. It is however possible that, in analogy with ribosomal A site, the binding of the antibiotics can shift the bulged-in/bulged-out equilibrium of flanking bases toward the bulged-out form.…”
Section: Comparison With Experimental Datamentioning
confidence: 96%
“…This widening confers the ability of the CC mismatch-containing helix to bind paromomycin, while the fully Watson-Crick counterpart with a narrower major groove shows no binding. Other RNA molecules that bind aminoglycosides and aminoglycoside analogs also bind at a site that is distorted from standard A-form RNA geometry (Fourmy et al 1996;Carter et al 2000;Vicens and Westhof 2001;Ennifar et al 2003;Raghunathan et al 2006) or have been found to widen its major groove upon binding (Staple et al 2008).…”
Section: Comparison With Other Rna-aminoglycoside Interactionsmentioning
confidence: 99%